Extended Yule-Walker identification of Varma models with single- or mixed frequency data - Peter A. Zadrozny (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
Chen and Zadrozny (1998) developed the linear extended Yule-Walker (XYW) method for determining the parameters of a vector autoregressive (VAR) model with available covariances of mixed-frequency observations on the variables of the model. If the parameters are determined uniquely for available population covariances, then, the VAR model is identified. The present paper extends the original XYW method to an extended XYW method for determining all ARMA parameters of a vector autoregressive moving-average (VARMA) model with available covariances of single- or mixed-frequency observations on the variables of the model. The paper proves that under conditions of stationarity, regularity, miniphaseness, controllability, observability, and diagonalizability on the parameters of the model, the parameters are determined uniquely with available population covariances of single- or mixed-frequency observations on the variables of the model, so that the VARMA model is identified with the single- or mixed-frequency covariances.
urn:nbn:de:hebis:30:3-392957
Keywords: C32; C80; 330; block-Vandermonde eigenvectors of block-companion state-transition; matrix of state-space representation; matrix spectral factorization